ANALISIS BIOMEKANIK GERAKAN TEMBAKAN TIGA ANGKA BOLA BASKET - Sayyid Agil Rifqi Munawar; Bangkit Seandi Taroreh; Mahir Dwi Nugroho; Yuniarti Sani Damayanti (Journal of Physical Education and Sport Science, 2024)
The three-point shot is a type of shot in basketball that has advantages. The advantage in question is in terms of points. When compared to other types of shots in basketball, the three-point shot has the most points, namely three points. If the three-point shot can be maximized in every match, it will be one of the keys to victory for a basketball team. The aim of this research is to determine the results of motion analysis of three-point shots using the Dartfish and Kinovea applications. This research uses a quantitative-qualitative descriptive research design with sampling using purposive sampling. A successful three-point shot made by a player with an average height of 1.77 m for State University of Malang basketball players had an arm angle of 82.17 degrees, a foot angle of 93 degrees, a ball elevation angle of 49 degrees, a maximum height of the ball of 4.45 m and a speed of 8 m/s.